Does embedding learning supports enhance transfer during game-based learning?. (February 2022) - Bainbridge, Katie; Shute, Valerie; Rahimi, Seyedahmad; Liu, Zhichun; Slater, Stefan; Baker, Ryan S.; D'Mello, Sidney K.
Abstract: Educational video games are hypothesized to be good environments for promoting learning; however, research on conceptual learning from games is mixed. We tested whether embedding a learning support in the form of short animations illustrating physics concepts that can be used to aid gameplay improved learning. Ninety-six 7th to 11th grade students were randomly assigned to play Physics Playground with or without the learning supports over a 4-day period. Results indicate that students who played a version of the game with embedded learning supports showed more improvement on a far- ( d = 0.36), but not on a near-transfer physics assessment ( d = 0.17) compared to those who played without the supports. The learning supports did not affect students' enjoyment with the game. We conclude that the game-embedded animations were effective at promoting conceptual learning without sacrificing the fun of game-based learning. Highlights: Studies show learning supports (LS) can improve educational game outcomes, but can hurt enjoyment. We tested an embedded LS in a Physics game with secondary school students. LS group had greater far transfer on a posttest than active controls. Overall gain and far transfer gain correlated with duration of exposure to supports. LS group did not report less enjoyment than the active control group.